2013
DOI: 10.1121/1.4805896
|View full text |Cite
|
Sign up to set email alerts
|

Monterey Bay ambient noise profiles using underwater gliders

Abstract: In 2012, during two separate week-long deployments, underwater gliders outfitted with external hydrophones profiled the upper 100-200 m of the Monterey Bay. The environment contained various noises made by marine mammals, ships, winds, and earthquakes. Unlike hydrophone receivers moored to a fixed location, moving gliders measure noise variability across a wide terrain. However, underwater mobile systems have limitations such as instrument and flow noise, that are undesired. In order to estimate the system noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Its possible noise sources, such as the air bladder, fin steering, battery movement and volume piston are described in [21]. Chandrayadula et al [11] showed that high-intensity sounds such as the sloshing of the glider at the sea surface, the bladder pump, the ballast pump, and the battery packs moving around are all broadband in nature. The bulk of the broadband noises were concentrated at the lower frequencies 0-3 kHz.…”
Section: Noise Sources Of the Underwater Glidermentioning
confidence: 99%
See 1 more Smart Citation
“…Its possible noise sources, such as the air bladder, fin steering, battery movement and volume piston are described in [21]. Chandrayadula et al [11] showed that high-intensity sounds such as the sloshing of the glider at the sea surface, the bladder pump, the ballast pump, and the battery packs moving around are all broadband in nature. The bulk of the broadband noises were concentrated at the lower frequencies 0-3 kHz.…”
Section: Noise Sources Of the Underwater Glidermentioning
confidence: 99%
“…Among these platforms, underwater gliders have been actively used for measurement of environmental underwater ambient noise. The addition of a single hydrophone sensor to an underwater glider provides a capability for measurement of underwater noise level [7][8][9][10][11][12][13][14] and the addition of a hydrophone array enables surveillance of the underwater acoustic environment [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…While the ROV is designed to make mobile acoustic measurements in the immediate vicinity of an MRE device, the presence of a tether can cause unwanted complications when operating in the vicinity of MRE devices consisting of several berths, connected with tendon-like cables. Additionally, given the low noise emitted by MRE devices, the presence of multiple thrusters and ballast pumps can significantly reduce the signal-to-noise ratio, a problem common in glider-based acoustic measurement platforms [7]. Furthermore, location estimation using a single pressure-only hydrophone remains a challenge, and the engineering costs involved in designing, maintaining, and deploying an ROV can be significant.…”
Section: Introductionmentioning
confidence: 99%